(untitled) (Biosaintifika: Journal of Biology & Biology Education, 2026)
Alopecia disrupts hair growth, leading to hair loss and baldness. Hypoxia-induced mesenchymal stem cell (MSC)–derived exosomes have emerged as a promising therapeutic alternative. These exosomes can modulate inflammatory responses and potentially enhance the expression of TGF-β and PDGF, key growth factors involved in hair follicle regeneration. This study aims to investigate the effects of hypoxia-induced MSC exosomes on TGF-β and PDGF expression in a fluconazole-induced alopecia-like rat model. Five groups were used: K1 (healthy control), K2 (fluconazole-induced, 0.9% NaCl), K3 (Minoxidil), K4 (100 µL hypoxia-induced MSC exosomes), and K5 (200 µL hypoxia-induced MSC exosomes). Skin samples were collected on day 15 post-treatment for analysis of TGF-β and PDGF levels using enzyme-linked immunosorbent assay (ELISA). Based on the analysis, the highest levels of TGF-β and PDGF were found in K1, followed by K5 and K4, while the lowest levels were observed in K2. This study finds that the single-dose injection of 200 µl of EH-MSCs daily for 14 days significantly increases the levels of TGF-β and PDGF in the skin, which contributes to improved hair growth. This study assumes that TGF-β and PDGF potentially improve hair growth through immunomodulation and a pro-angiogenic mechanism. These findings suggest that hypoxia-induced MSC exosomes represent a promising therapeutic strategy for alopecia and may be developed broadly for regenerative medicine targeting chronic inflammation-based skin disorders. However, further studies are needed to explore more about various cytokine and their function that relevance for alopecia and other inflammation-related skin conditions.